Pengaruh Tata Kelola Pemerintah Terhadap Kemiskinan di Negara-Negara ASEAN - Ramadhan, Azmi Ilham; Riani, Novya Zulva (Universitas Negeri Padang, 2024)
This study aims to analyze the influence of government governance on poverty in ASEAN countries. This research is descriptive and associative type. The data used is secondary data from 8 countries in ASEAN in 2011-2020 obtained from the Asean Development Bank and the Worldwide Governance Indicators (WGI) of the World Bank with government governance variables divided into four dimensions, namely corruption control, political stability and absence of violance/ terrorism, quality of regulation, voice and accountability. This study uses panel data regression with the Fixed Effect Model approach assisted by Eviews 10. The results show that government governance simultaneously has a significant effect on poverty with the following details: 1) Control of corruption has a negative and insignificant effect on poverty in countries -ASEAN countries, 2) Political stability and the absence of violance/terrorism have a negative and significant effect on poverty in ASEAN countries, 3) Regulatory quality has a negative effect and there is no significant effect on poverty in ASEAN countries, 4) Voice and accountability have an effect positive and not significant to poverty in ASEAN countries.